Constructing “Singaporeanness” in universities: how is the Singaporean identity negotiated by foreigners and first-generation Singaporeans? - Tee, Isaiah Yuan Cheng (2017)
This thesis aims to study how a Singaporean identity is negotiated by foreigners and first-generation Singaporeans in universities. This identity is negotiated through what this thesis dubs as Singaporeanness, a set of defining Singaporean characteristics or traits. Using Swann’s Identity Negotiation Model, focusing particularly on the target’s side of the model, twelve participants are interviewed on how they construct Singaporeanness for themselves, and the motivations behind the negotiation. It was found that among the qualities listed, the use of language, specifically Singlish, proved to be a salient negotiation strategy. It is thus plausible to consider that a more holistic approach to a Singaporean identity would be more effective, embracing not only a top-down approach, but also the bottom-up, more organic approach as well.